Multi-criteria decision analysis of classrooms standardisation in a higher education institution - Salomon, Valério A.P. [UNESP]; Alonso, Pedro J.; Marins, Fernando Augusto Silva [UNESP] (Inderscience Publishers, 2016)
As any other organisation, a higher education institution (HEI) has to manage operations and processes when transforming inputs in outputs. Furniture used in laboratories, offices, and even in the classrooms is an important resource. When there are two or more feasible alternatives for furniture, choosing the best furniture becomes a decision problem. One can make a mono-criterion decision based only on costs. However, furniture selection can be modelled as a multi-criteria decision problem, incorporating attributes as user's comfort and space usage. A multi-criteria decision analysis (MCDA) methodological framework is presented comprising structuring, measurement, and synthesis. This work presents how a Brazilian HEI applied an MCDA method to standardise furniture to its classrooms. analytic hierarchy process was applied and the original structuring model benefits-opportunities-costs-risks was adapted. The use of four criteria requiring different types of information (two qualitative criteria and two quantitative criteria) enhances the learning of MCDA, which is a major contribution of this paper.
Keywords: AHP; Analytic hierarchy process; Higher education; MCDA; Multi-criteria decision analysis